Sustainable economic analysis and length weight relationship of Bullet Tuna (Auxis rochei) fishery in east area of Bali Strait, Indonesia - GATUT BINTORO; DARMAWAN O. SUTJIPTO; TRI D. LELONO; BAMBANG SEMEDI; AIDA SARTIMBUL; MITA T. WAHYUNI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Bintoro G, Sutjipto DO, Lelono TD, Semedi B, Sartimbul A, Wahyuni MT. 2023. Sustainable economic analysis and length weight relationship of Bullet Tuna (Auxis rochei) fishery in east area of Bali Strait, Indonesia. Biodiversitas 24: 3528-3535. Bullet tuna (Auxis rochei) is a small pelagic fish with an important economic value and is mainly caught by fishermen in the east area of Bali Strait, Indonesia. The high market demand for this fish has increased fishing efforts to achieve maximum catch, and this uncontrolled fishing activity will threaten its sustainability and economic potential. This study was conducted to determine stock status both biologically and economically. The length-weight relationship was calculated by measuring the length and weight of 1,200 samples of fish landed in the Pengambengan Archipelago Fishing Port (AFP) in Jembrana Bali Province from February to March 2020. The calculation of maximum sustainable yield (MSY), maximum economic yield (MEY), and equilibrium of open access (OA) were done by using secondary catch data from 2008 to 2019. Gordon Schaefer’s model analysis found that the values of YMSY and fMSY were 3,314 tonnes year-1 and 3,503 trips year-1, respectively. While the values of YMEY and fMEY were 3,160 tonnes year-1 and 2,750 trips year-1, respectively, which gave a maximum profit of about 1.4 billion USD year-1. In addition, the equilibrium of OA would be achieved when the fishing effort reaches 5,500 trips year-1 and the amount of catch reaches 2,237 tons year-1. The growth pattern of the bullet tuna was isometric, which indicates that the bullet tuna in the east area of Bali Strait has a proportional body shape. The utilization status of bullet tuna (A. rochei) is over-exploited.